Pendidikan Kewarganegaraan Sebagai Wahana Dalam Mempersiapkan Warga Negara Muda Yang Smart And Good Digital Citizenship - Abiyuna, Thaufan (Jurnal Civic Hukum, 2023)
This study aims to place Civic Education proportionally as the right vehicle in preparing young citizens who are smart and good digital citizenship in the development of science and technology in the era of digital communication. The method used in this study is qualitative with data collection through interviews, observations, and documentation. With the results of conceptual research, there are differences in meaning between digital citizenship, digital citizens, and digital citizenship education. In today's digital era, the development of digital civic education in Indonesia should be a must. This is because the current era of digitalization has had a tremendous disruption impact on various aspects of people's lives, including in the world of education. However, the development of digital citizenship education in Indonesia must certainly look at various aspects of the opportunities and challenges that exist.